Pengaruh Kompensasi, Motivasi, dan Komitmen Organisasi terhadap Prestasi Kerja Karyawan - Fitriyatul Hiqmah (Jurnal Ekonomi Akuntansi dan Manajemen, 2016)
Research this aim to analyze the influence of compensation, motivation, and organization commitment to employees labour capacity of Bank Mandiri, Inc. Respondents of this research were all employees, with which 30 samples with sampling technique is purposive sampling. This research uses primary data obtained directly via a questionnaire. Data analysis techniques to test the hypothesis of this research is double regression analysis. The result of this research and hypothesis testing show that compensation, motivation and organization commitment have the influence to labour capacity employees. From third free variable, motivation variable have influence larger ones to employees labour capacity. Keywords: compensation, motivation, organization commitment, employees labour capacity